EFEK LAMA WAKTU PEMAPARAN OBAT NYAMUK BAKAR TERHADAP MAKROSKOPIS PARU MENCIT (Mus musculus) - Acivrida Mega Charisma; Refilda Refilda Ningtyas (Poltekkes Kemenkes Pakassar, 2021)
The active substances contained in mosquito coils when used long term can affect and cause abnormalities in the organs of the human body, one of which is the lungs. The purpose of this study was to determine the effect of exposure time for mosquito coils on microscopic and macroscopic examination of the lungs of mice (mus musculus). The research was experimental with 24 mice divided into four groups, namely P0 as a control, P1 exposed to mosquito coil smoke for 4 hours, P2 exposed to smoke for 6 hours, and P3 exposed to smoke for 8 hours per day for 30 days. On the 30th day, surgery was performed to perform macroscopic observations which included weighing the lungs, measuring the diameter of the lungs and observing the color of the lungs. The results of the research P0, P1, P2, and P3 on color microscopic showed pink; pink with raised patches; red with dark patches; and red with white patches. At P0, P1, P2, and P3 lung diameters, the results were 1.3; 1.4; 1.5; 1.6. Meanwhile, the lung weight obtained was 0.22; 0.24; 0.24; and 0.24. The conclusion in this study is that there is a significant difference in the duration of exposure to mosquito coils on lung diameter.